(untitled) (Communications in Computational Chemistry, 2025)
The fixation of CO_2 is a promising carbon-neutral approach and drawing lots of attention in the past decades. Among lots of fixation of CO_2 methods, the cycloaddition of CO_2 into epoxides (CCE) reaction is important because it could generate high value-added products. Recently, employing chalcogen bonding (ChB) catalysts for the CCE reaction has been proposed and offers significant advantages of low price, environmental friendliness, and ease of recycling. In this work, the ChB catalyzed the CCE reaction is investigated by high level theoretical calculations. The reaction can be divided into three subprocesses: ring-opening, nucleophilic addition, and formation of cyclic carbonate. Both Se- and Te-based ChB catalysts have shown the potential for catalyzing the CCE reaction, the overall catalytic performance of Te-based catalysts was superior to the Se-based ones. Overall, the most positive electrostatic potentials of the ChB catalysts, electrostatic term of the ChB binding energies, electron density at the ChB critical points, and electron density difference play important roles in the ChB catalyzed CCE reaction. This work elucidated the ChB catalyzed mechanism of the CCE reaction and provided theoretical guidance for the future development of efficient ChB catalysts for the CCE reaction.